(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article reveals the content and essence of the development of the skills of observation, diligence, logical thinking, creative activity and the implementation of knowledge in everyday life through practical training of students in geography lessons. Examples are given on the organization of practical training and methods of solving issues.